Castleman disease: A single-center case series in Nepal Mediciti Hospital - Acharya, Shoshan; Aryal, Gopi; Basnet, Sunila; Rana, Reena; Pandey, Kricha; Thakur, Nikki (Nepal Mediciti Medical Journal, 2024)
BACKGROUND In 1954, Castleman Disease (CD), was first described and is also known as angiofollicular lymph node hyperplasia or giant lymph node hyperplasia . Among many sites where lesion occurs, commonest is in the thorax (60%), abdomen (11%), neck (14%), and axilla (4%) MATERIALS AND METHOD We analyzed five cases of Castleman disease we received in Nepal Mediciti during five-year period from 2020 to 2024. Demographics, clinical variables, anatomical site, centricity, histopathology, immunochemistry, and surgical approach were reviewed. RESULTS Among five cases, anatomical location of two cases from retroperitoneum, two from inguinal region and one is from cervical lymph node. Three cases were male and two were female. Age group of these five cases shows three were adult and two were children. All of them underwent surgical resection and under continuous follow up. One of the cases from retroperitoneum had got recurrence. CONCLUSION Castleman disease is a diagnosis of exclusion. Case should be evaluated on the basis of proper clinical findings, blood parameters, HIV and HHV-8 test, imaging along with biopsy and IHC. Lymphoma and Kaposi sarcoma may mimic on radiology and histologically with Castleman disease.